Economic and energy estimation of the effect of seeding rates of spring peas in the south of the Rostov region - S. A. Vasilchenko; G. V. Metlina; A. R. Ashiev; N. S. Kravchenko (Зерновое хозяйство России)
For Russia, peas are traditional legumes, used both in the food industry for its excellent taste, and in animal husbandry for the high content of feed units and balanced protein, which allows reducing the cost of animals’ feeding. The purpose of the current study was to estimate the effect of the seeding rates of peas on its productivity, feed value of its beans, economic and bioenergetic cultivation efficiency. The current paper has presented the study results obtained in the laboratory for cultivation technology of row crops (FSBSI “Agricultural Research Center “Donskoy”) in 2019–2020 where there was studied the effect of seeding rates on productivity of the middle maturing pea variety ‘Aksaysky Usatii 5’ of the Don breeding. The soil of the experimental plot was favorable for growing peas with 3.36% of humus in the arable, with 7.0 pH, 24.4 mg/kg of soil of P2O5, 360 mg/kg of soil of K2O. The studied seeding rates influenced yield structure elements of peas, protein percentage in seeds and yield of feed units. At seeding rates of 1.2-1.8 million of germinating seeds per hectare, there was an increase in protein percentage in seeds on more than 1.0% in comparison with the norms of 0.8-1.0 million of germinating seeds per hectare. In the same variants of the trial, the yield of digestible protein was at the level of 528-579 kg/ha, compared with that of 390-456 kg/ha when sown with a rate of 0.8-1.0 million of germinating seeds per hectare. The maximum productivity (2.07 t/ha) was recorded with a seeding rate of 1.4 million of germinating seeds per hectare. In the same variant of the trial, there were identified the maximum indicators of energy and economic efficiency, such as 2.07 of energy efficiency coefficient and 97.4% of profitability with the lowest production cost of 7600 rubles/ton.